Division of labour in the domestic arena in dual-career households. - Kaur, Arvinder. (2012)
This paper explores the division of labour with regard to housework and childcare amongst dual-career couples in Singapore. I draw on data from interviews conducted with individuals who are married, and both they and their spouse engage in paid employment. The main findings suggest that the division of labour amongst these households depends on the race of the individuals, with the Malay and Chinese respondents being more egalitarian and the Indian respondents subscribing to the belief that women are responsible for the domestic arena.